O Oriente Médio Antigo: eurocentrismo, deportação e ensino de história - Rebêlo, Samir de Barros (2023)
This dissertation intends to contribute to the teaching of History, through a Textual Corpus (website) “historiasconectadas.com.br”. The master's thesis seeks different perspectives, diversity, cultural interrelationships and school awareness. The main themes in question are related to the Eurocentrism present in the daily life of Basic Education, and within Ancient History. European ethnocentrism is analyzed from a general point of view, and also from a specific point of view, when glimpsing the crisis of Ancient History. Through the “Connected Stories”, allied to Global History, a detailed research was developed on the cultural relations between Assyria and Babylon of the 8th, 7th and 6th centuries BC, associated with the phenomenon of the deportation of the statue of Marduk, in order to understand the products derived from intense contact, in contrast to the universalist (Eurocentric) vision. It is essential to demonstrate how the research integrates with the parameters of the National Common Curricular Base (NCCB). Regarding the convergence of teaching and learning in conformation with scientific research, Paulo Freire's pedagogical perspective was taken into account, aiming at dialogue, curiosity, criticism and freedom and love for teaching. Apply the educational product, “historiasconectadas.com.br”, at IEMA – Integrated Vocational Unit in the State of Ceará, located in the Coheb neighborhood of Sacavém – for the 3rd year of High School. Keywords: